La genèse de l’éco-conception en Chine dans le secteur des TIC, une exportation européenne - Dai Yue Huang; Chao Liu; Laura Draetta; Gilles Puel (VertigO)
This paper presents the first results of an empirical research on the emerging practices of eco-design in the field of information technology and communication (ICT) in China. It shows that the structuring of the organizational field of eco-design was commissioned by external actors-networks, mainly the European regulatory constraints. The central government, with the relay of the major exporting companies in the sector, was taken to build an eco-system of eco-design combining economic efficiency and incentive regulation to serve both strategic-utilisation set and meet global demand environmentalist.